The Influence of Internet of Things (IoT) on Operational Efficiency and Competitive Advantage in the Information Technology Industry in Indonesia - Judijanto, Loso; Triwiyatno, Aris; Sofyan, Sofyan (The Eastasouth Journal of Information System and Computer Science, 2024)
This study investigates the impact of Internet of Things (IoT) adoption on operational efficiency and competitive advantage within the Information Technology (IT) industry in Indonesia. A quantitative research approach was employed, utilizing a cross-sectional survey design to collect primary data from 170 IT companies operating in Indonesia. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) algorithm was utilized to analyze the data and test the research hypotheses. The findings reveal that IoT adoption positively influences both operational efficiency and competitive advantage within the Indonesian IT industry. These results underscore the transformative potential of IoT technologies in enhancing organizational performance and strategic positioning in the digital era. The study contributes to the existing literature by providing empirical evidence on the benefits of IoT adoption in the context of the Indonesian IT industry, offering insights for policymakers, practitioners, and researchers seeking to harness the potential of IoT technologies for sustainable growth and innovation.